2017
DOI: 10.1016/j.desal.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin based biomimetic membrane in forward osmosis: Chemical cleaning resistance and practical operation

Abstract: CitationLi Z, Valladares Linares R, Bucs S, Fortunato L, Hélix-Nielsen C, et al. (2017) Aquaporin based biomimetic membrane in forward osmosis: Chemical cleaning resistance and practical operation. Desalination 420: 208-215. Available: http://dx. AbstractAquaporin plays a promising role to prepare a high performance biomimetic forward osmosis membrane. However, aquaporin as a protein also has a risk of denaturation caused by various chemicals, resulting in a possible decay of membrane performance. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…On the one hand, similar to SDS, SDBS can form micelles at C2 and C3 levels since the critical micelle concentration of SDBS is 1.1 mmol L –1 . On the other hand, surfactants could reduce membrane surface tension, which improved the hydrophilicity the membrane surface . As shown in Table , the decrease in contact angle after the test of SDBS indicated that the hydrophilicity of the membrane surface was indeed significantly increased.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, similar to SDS, SDBS can form micelles at C2 and C3 levels since the critical micelle concentration of SDBS is 1.1 mmol L –1 . On the other hand, surfactants could reduce membrane surface tension, which improved the hydrophilicity the membrane surface . As shown in Table , the decrease in contact angle after the test of SDBS indicated that the hydrophilicity of the membrane surface was indeed significantly increased.…”
Section: Resultsmentioning
confidence: 99%
“…Forward osmosis (FO) is recognized as an emerging membrane separation technology which has the advantages of low energy consumption and high rejection of a broad range of pollutants . FO uses the osmotic pressure gradient as the driving force for the transport of water across the semi‐permeable membrane from a relatively low concentration feed solution (FS) to a concentrated draw solution (DS) and consequently resulting in concentration of the FS and dilution of the DS . A good FO membrane should have excellent water flux, high salt rejection and superb membrane stability simultaneously …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations